MODEL PEMILIHAN MODA ANTARA MOBIL PRIBADI DAN BIS TRANSJOGJA AKIBAT PENERAPAN BIAYA KEMACETAN - Sugiyanto, Gito; Malkhamah, Siti (Jurnal Transportasi, 2009)
Traffic congestion can be a serious problem in major cities around the world, especially in centrall urban area. Congestion results not only in time lost while sitting in traffic jams but also constitutes a disruption to company supply chains and the general flow of commerce. Idling vehicles contribute as well to air pollution which reduces the quality of health. The aim of this paper is to formulate mode choice model between privatepassenger cars and TransJogja Bus service as a result of the application of a congestion cost in a congested road along the region of Malioboro, Yogyakarta. The amount of the congestion cost represents the difference between perceived and actual generalized cost in traffic jam condition. In this study the congestion cost is only applied to the private passenger cars, as they are expected to shift to TransJogja Bus and, therefore, thepublic transport usage will increas. The mode choice model was developed based on users preferences of service as indicated by travel attributes. The logit binomial model was used to formulate the individual behavior based on stated preference data from passenger car users in Malioboro, Yogyakarta. The modelpredicts the probability of choosing a particular mode of transportation. The result show that five travel attributes assumed to have high influences toward mode choice behavior. These attributes are travel cost, congestion cost, travel time, parking cost, and walking time to the bus stop of TransJogja.Keywords: binomial logit model, congestion cost, stated preference, traffic congestion, TransJogja